(untitled) - MacDonald, Robert W. (Hoboken, N.J., 2008)
Beat the System is a follow-up to Robert MacDonald's controversial but successful first book, Cheat to Win. Packed with proven, real-life advice, Beat the System shows readers how to deal with the bureaucracy that can smother the creativity and entrepreneurship essential to long-range business success. Beat the System teaches readers how to beat the bureaucratic system by building entrepreneurial cultures in their businesses, their departments, or even their individual jobs. MacDonald skillfully describes how business cultures develop, how bureaucratic procedures and processes seep into them, and how to build an entrepreneurial culture even as we live in a bureaucratic world. At the heart of his system are practical steps that create a sense of ownership among employees, invites their participation, creates a common mission, fosters an entrepreneurial atmosphere, and shares the rewards with all.
Keywords: Entrepreneurship,Bureaucracy,Doanh nhân,Quan liêu; United States,United States,Hoa Kỳ,Hoa Kỳ